THE RELATIONSHIP BETWEEN FLEXIBLE WORKING ARRANGEMENT AND JOB SATISFACTION MEDIATED BY WORK-LIFE BALANCE IN PT. TIARA IMPRESA GUGUS ARTHA - Nurhidayah, Ade; Herlitah; Nurjanah, Siti (Faculty of Economics and Business, Universitas Negeri Jakarta, 2022)
This study aims to determine the relationship between Flexible Working Arrangement (X1) and Job Satisfaction (Y) mediated by Work-life Balance (Z) at PT Tiara Impresa Gugus Artha. This research was conducted for six months starting from December 2020 to June 2021. The research method used was a survey method. The affordable population in this study amounted to 110 employees. Based on Isaac and Michael's table, the number of samples in this study was 86 respondents. The sampling technique used is simple random sampling technique. The data analysis techniques used are: (1) analysis requirements test which consists of validity and reliability tests. The test results state that the three variables are valid with reliable values for the job satisfaction variable, namely 0.867, the flexible working arrangement variable, 0.706 and the work-life balance variable 0.840; (2) Model suitability test consisting of absolute fit indices, incremental fit indices and parsimony fit indices. The test results stated that the three variables were fit; (4) The hypothesis test in this study used SEM AMOS 21. In this study, the detection test of the intervening variable was carried out using the Sobel test. The results show that work-life balance mediates the relationship between flexible working arrangements and job satisfaction.